Three-Dimensional Nonlinear Dynamic Analysis of Base Isolated Cylindrical Steel Tank - Abdellali Saria; Mohamed Djermane; Nasser Dine Hadj-Djelloul (Civil Engineering Journal, 2022)
Failure of a tank during an earthquake can result in significant financial, human, and environmental losses. Thus, their lack of resiliency against strong earthquakes may result in refinery disruption. This has the potential to have a considerable impact on any economic system. As a result, more research into the seismic performance of tank structures is required to attain the highest possible level of resistance against strong earthquakes. In this paper, we aim to look into the installation of seismic isolation systems in cylindrical steel storage tanks. A nonlinear 3D finite element model is developed with ANSYS software. Moreover, tank wall material nonlinearity, fluid-structure-interaction, and sloshing components are considered. The bilinear hysteretic LRB is used for modal and time-history analysis. In this work, three tanks with varying aspect ratios are studied: "Model A", "Model B", and "Model C". Furthermore, the fixed tank's fundamental frequencies were compared to the analytical results of the American API 650 Standard. Subsequently, the dynamic behavior response of the researched tanks to the horizontal component of the El-Centro 1940 earthquake with PGAs of 0.34g and 0.5g is investigated. As a result, the dominating frequency of the seismic isolation system is within the effective frequency range of seismically isolated systems. The results illustrate that the base isolation limits the tank wall movement with a large displacement in the isolators; the mode shape is a cantilever beam in all isolated circumstances. The total seismic response reduction in the slender tanks is greater as compared to the broad case in the base-isolated tanks. The sloshing displacement increases with an increase in the tank aspect ratio. Additionally, the isolation device eliminates tank buckling at the base and top of the tank shell during seismic excitation (elephant foot and diamond buckling). It can be concluded that the seismic isolation technique has a more significant impact on reducing the dynamic response of ground-supported tanks, particularly in taller tanks as compared to broad tanks. Doi: 10.28991/CEJ-2022-08-06-013 Full Text: PDF